The activation of multiple slip systems in polycrystalline zirconium by using automated lattice rotation framework - Huigang Shi; Jianye Chen; Junqiang Lu; Libing Zhu; Lefu Zhang; Jiuxiao Li; Weijie Lu; Xianglong Guo (Materials Research Letters)
Understanding the deformation mechanism in polycrystalline metals is critical to use them in high-value high-risk applications. Here, we report an automated framework based on lattice rotation analysis for accurately identifying slip system and assessing the multiple slip activities in large data set of polycrystalline Zr, aims to statistically provide deep insight on deformation mechanism of Zr. Results show that multiple slip is the dominant slip system rather than single slip system. This method can be applied as a complementary method to the intragranular misorientation axis (IGMA) method and can act as bridges between macro-mechanical response and microstructural deformation mechanisms.